A target sample of adolescents and reward processing: same neural and behavioral correlates engaged in common paradigms? - Nees, Frauke; Vollstädt-Klein, Sabine; Fauth-Bühler, Mira; Mann, Karl; Poustka, Luise; Banaschewski, Tobias; Rietschel, Marcella; Struve, Maren; Flor, Herta (Experimental brain research, 2012)
Adolescence is a transition period that is assumed to be characterized by increased sensitivity to reward. While there is growing research on reward processing in adolescents, investigations into the engagement of brain regions under different reward-related conditions in one sample of healthy adolescents, especially in a target age group, are missing. We aimed to identify brain regions preferentially activated in a reaction time task (monetary incentive delay (MID) task) and a simple guessing task (SGT) in a sample of 14-year-old adolescents (N = 54) using two commonly used reward paradigms. Functional magnetic resonance imaging was employed during the MID with big versus small versus no win conditions and the SGT with big versus small win and big versus small loss conditions. Analyses focused on changes in blood oxygen level-dependent contrasts during reward and punishment processing in anticipation and feedback phases. We found clear magnitude-sensitive response in reward-related brain regions such as the ventral striatum during anticipation in the MID task, but not in the SGT. This was also true for reaction times. The feedback phase showed clear reward-related, but magnitude-independent, response patterns, for example in the anterior cingulate cortex, in both tasks. Our findings highlight neural and behavioral response patterns engaged in two different reward paradigms in one sample of 14-year-old healthy adolescents and might be important for reference in future studies investigating reward and punishment processing in a target age group.